Critical Discourse Analysis On “Spiderman” - Armelia, Lisa (Syntax Literate, 2019)
Talking about CDA or “Critical Discourse Analysis” means talking about power domination, ideologies and concepts employ in certain community. The reflection of power, ideologies, concepts or event traditional values can be found easily nowadays in the entertainment section with products like movies, songs, advertising, and many more. Since the values are packed with attractive features, some people are allured with the features and forget the power that drives some people to create the products which enable them to portray their beliefs and values. This research is trying to reveal the critical aspect of the movie “Spiderman” (2002) which contain Christian beliefs, bias concepts in American’s humanity and heroism. The method employs in the research is descriptive analysis based on the data taken from the scenes of the movie, tagline, dialogues. The result shows that through this movie, American unveils the ideology of liberalism covered with the values of humanity and heroism to drive people into the hegemony: American is the only power domination and the source of great heroes.